The local stratification preconditions the marine heatwaves in the Yellow Sea - Lee, Eun Young; Lee, Dong Eun; Park, Young-Gyu; Kang, Hyunjin; Baek, Haedo (Frontiers in Marine Science, 2023)
Vertical stratification preconditions marine heat wave (MHW) events in marginal seas. The major events since 1982 in the marginal sea area west and south of the Korean Peninsula have been led by abnormally strong stratification in the vicinity, which was detected at least two months in advance. This robust coincidence provides substantial control over mid-summer events through local stratification in early summer. Such heatwave-leading stratification can be attributed to various oceanic factors during early summers, including anomalous sea surface temperature, freshwater flux, and wind mixing. Knockout-style experiments using a 1-dimensional ocean model revealed that the upper ocean stratification in the preceding months, mostly through wind mixing, is capable of regulating MHWs. Meanwhile, in the longer historical records, gradual decreases in the intensity and frequency of the daily wind gusts were found, possibly as a mixed result of anthropogenically induced climate change and strong natural variability of the midlatitudes. This might have dominated in enhancing the occurrence of MHWs, combined with the rising background surface temperature.